2014
DOI: 10.1093/nar/gku638
|View full text |Cite
|
Sign up to set email alerts
|

The PARP inhibitor Olaparib disrupts base excision repair of 5-aza-2′-deoxycytidine lesions

Abstract: Decitabine (5-aza-2′-deoxycytidine, 5-azadC) is used in the treatment of Myelodysplatic syndrome (MDS) and Acute Myeloid Leukemia (AML). Its mechanism of action is thought to involve reactivation of genes implicated in differentiation and transformation, as well as induction of DNA damage by trapping DNA methyltranferases (DNMT) to DNA. We demonstrate for the first time that base excision repair (BER) recognizes 5-azadC-induced lesions in DNA and mediates repair. We find that BER (XRCC1) deficient cells are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 42 publications
11
87
0
Order By: Relevance
“…a minor fraction of zebularine-induced damage is repaired by NER or SSA, which is also consistent with our HR data. This contrasts with the effects of 5-azacytidine, where NER is the dominant repair pathway in bacteria and humans (Salem et al, 2009;Orta et al, 2014). Because the smc6b mutant was more sensitive to zebularine than to other tested drugs, we suggest that the SMC5-SMC6 complex plays an essential role in the repair of zebularine-induced NPAs in Arabidopsis.…”
Section: Discussionmentioning
confidence: 64%
“…a minor fraction of zebularine-induced damage is repaired by NER or SSA, which is also consistent with our HR data. This contrasts with the effects of 5-azacytidine, where NER is the dominant repair pathway in bacteria and humans (Salem et al, 2009;Orta et al, 2014). Because the smc6b mutant was more sensitive to zebularine than to other tested drugs, we suggest that the SMC5-SMC6 complex plays an essential role in the repair of zebularine-induced NPAs in Arabidopsis.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, a recent study has demonstrated that XRCC1 mutant cells, defective in BER, are hypersensitive to aza-dCyd and this phenotype is associated with an accumulation of abasic sites and DNA strand breaks in genomic DNA (11). It is therefore possible that some of these breaks are an indication of the formation of DNA repair intermediates induced by the presence of uracil and aza-uracil.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cytotoxic and mutagenic properties of decitabine may be partially derived from its intrinsic chemical instability once it is incorporated into DNA or by the accumulation of DNA repair intermediates (3). Recently, it has been proposed that the base excision repair mechanism (BER) might be initiating the repair of decitabine-induced DNA base lesions although the precise nature of the damage or the DNA glycosylases involved remains unknown (11).…”
Section: Introductionmentioning
confidence: 99%
“…CCC have been assumed to demonstrate an increased reliance on the HNF-1β-CHEK1 axis for cell survival (49). Significant genes involved in synthetic lethality with CHEK1 are reported to be ATR, MYC, TP53, WEE1 and CDKN1A (29,(61)(62)(63). ATR inhibition is currently assessed in early-phase clinical trials as single agents and in combination strategies, including PARP inhibitors (37).…”
Section: Discussionmentioning
confidence: 99%